Intermodal and Intermedial Translation of Songs in Stage and Film Musicals: Application of an Integrated Approach in Turkish Context - Neslihan Kansu-yetkiner; Mehmet Şahin (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Engaging with a spectrum of intermodal and intermedial translation, the primary aim of this study is to present and apply a holistic multimodal approach to song translation through which the interaction of the potential meaning of semiotic resources can be considered as a composite and indivisible whole. The focus of this study is Fiddler on the Roof, chosen because it has been translated for both stage and film musicals in Turkiye. With this purpose, we adopted a triple model which operationalized Halliday’s Systemic Functional Grammar (SFG), Kress and van Leeuwen’s integrated approach by combining textual and visual grammar, and Leeuwen’s (1999) framework of musical analysis. Our historical approach to the Turkish musical landscape proposes that translation strategies for songs in film musicals reflect a consistent pattern of choice (mainly mixed translation) arising from state-monopolized TV impositions; while in contrast, for stage musicals, the wider range of translation strategies shed light on fluctuations in multi-semiotic popular arts entertainment, caused by ideologically- and economically-driven practices. Our in-depth multimodal analysis revealed that an integrated approach can bring to the surface the potential density of interacting semiosis in the performative and narrative dimensions of musicals. These new dimensions, enabled through a multimodal analysis, require new skills, knowledge and literacies, thus, expanding the boundaries of translation studies.